Uses and vulnerability of ligneous species exploited by local population of northern Burkina Faso in their adaptation strategies to changing environments - Ouédraogo, Pauline; Bationo, B. André; Sanou, Josias; Traoré, Salifou; Barry, Silamana; Dayamba, Sidzabda Djibril; Bayala, Jules; Ouédraogo, Mathieu; Soeters, Sebastiaan; Thiombiano, Adjima (Springer, 2017)
Arid and semi-arid areas of West Africa are highly subject to climate change effects. This is combined to other drivers such as population growth and livestock number increase. To cope with such changing environment, endogenous adaptation strategies of poor local communities rely on the use of natural resources through empirical knowledge. Unfortunately, these knowledge and practices are insufficiently known to policy makers, and this hampers their consideration in the elaboration of adaptation strategies. A household survey was conducted in the Sillia village in northern Burkina Faso using semi-structured interviews. This study identified most used (preferred) species in this changing environment together with their ethnobotanical use value (VUET).